Broad-band design techniques for transimpedance amplifiers - Lu, Zhenghao (2009)
In this paper, a novel bandwidth enhancement technique based on the combination of capacitive degeneration, broad-band matching network, and the regulated cascode (RGC) input stage is proposed and analyzed, which turns the transimpedance amplifier (TIA) design into a fifth-order low-pass filter with Butterworth response. This broad-band design methodology for TIAs is presented with an example implemented in CHRT 0.18-mum 1.8-V RF CMOS technology. Measurement data shows a -3-dB bandwidth of about 8 GHz with 0.25-pF photodiode capacitance. Comparing with the core RGC TIA without capacitive degeneration and broad-band matching network, this design achieves an overall bandwidth enhancement ratio of 3.6 with very small gain ripple. The transimpedance gain is 53 dBOmega with a group delay of 80plusmn20 ps. The chip consumes only 13.5-mW dc power and the measured average input-referred noise current spectral density is 18 pA/radicHz up to 10 GHz.